The Moltenos of the Cape - Molteno, Selina, 1940- author. Link
1 online resource (264 pages)
Keywords: This biography traces the extraordinary story of the Molteno family coming from an Anglo-Italian origin, whose legacy helped shape South African political and social life from the 19th century onward. At its centre stands Sir John Charles Molteno, the first prime minister of the Cape Colony, who fiercely defended South African interests against British colonial authority. Of his 19 children, five left a distinct imprint on history: Betty, a passionate political activist; Percy, a Liberal MP in the British Parliament; Charlie, a defender of Black voters' rights; James, Speaker of both the Cape and Union parliaments; and Barkly, a naval commander at the Battle of Jutland. Spanning continents and generations, the book chronicles their shared fight against racism, imperialism, and segregation-long before such ideas gained wider currency. A timely account of a remarkable family committed to justice, reform, and public service.Appeals to readers of political history, African studies, and biography, offering rare insights into a family that worked to unify and uplift a fractured society.The subject matter also includes: Introduces the rich historical biography of a multigenerational South African family with Anglo-Italian roots and deep political impact. Provides timely and inspiring narrative of anti-racism, reform, and public service. Includes major political and historical figures: from Sir John Charles Molteno to members of the British Parliament and leaders in the Cape and Union governments. Explores global and local history, including British imperialism, African resistance, women's rights, and naval warfare. Offers rare insights into a family that worked to unify and uplift a fractured society Print editions not for sale in Sub-Saharan Africa